Preparation method of waterborne polyurethane type super-hydrophobic composite coating

By using long-chain nanocellulose-loaded hydrophobic nanoparticles in the aqueous polyurethane type superhydrophobic composite coating and bonding with the aqueous polyurethane network, the problem of difficult to take into account in the prior art is solved, and high efficiency is achieved The hydrophobic and wear-resistant properties are suitable for a variety of substrate materials.

CN119264739APending Publication Date: 2025-01-07HUBEI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411529067.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

It is difficult to take into account the existing superhydrophobic coatings between improving hydrophobicity and wear resistance. Especially under the premise of environmental protection, how to enhance hydrophobicity and wear resistance is a challenge faced by technicians.

Method used

Long-chain nanocellulose-loaded hydrophobic nanoparticles are used and bonded to the aqueous polyurethane network to expose the nanoparticles to the surface. The aqueous polyurethane-type superhydrophobic composite coating is prepared by a simple spraying process.

Benefits of technology

It significantly improves the hydrophobic effect and wear resistance of the coating, achieves a hydrophobic effect of up to 162.3° and good mechanical wear resistance. It has a simple process, environmental protection and low production cost, and is suitable for a variety of substrate materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264739A_ABST
    Figure CN119264739A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a waterborne polyurethane type super-hydrophobic composite coating, which comprises the following steps: firstly preparing a dispersion liquid of nano-cellulose loaded hydrophobic nanoparticles, spraying waterborne polyurethane on a base material, then spraying the dispersion liquid of nano-cellulose loaded hydrophobic nanoparticles on a semi-dry waterborne polyurethane film, and drying to obtain the waterborne polyurethane type super-hydrophobic composite coating. And drying at room temperature to obtain the waterborne polyurethane type super-hydrophobic composite coating. According to the method, cellulose can be tightly combined with a waterborne polyurethane layer to enhance the wear resistance of the coating, and it is guaranteed that hydrophobic particles loaded on the cellulose are exposed on the surface of the coating as much as possible. And the method is simple, non-toxic and pollution-free, enhances the wear resistance of the hydrophobic coating, can be used for water gathering devices, coating of offshore wind power devices, anti-corrosion steel frameworks and the like, and can be used for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite coatings, and in particular to a method for preparing a waterborne polyurethane type super-hydrophobic composite coating. Background Art

[0002] At present, many super-hydrophobic coatings use fluorine-containing long chains as hydrophobic modifiers, and the modified nanoparticles are directly combined with water-based polyurethane, which makes it difficult to balance the hydrophobicity and wear resistance of the hydrophobic coating. The effective hydrophobic component embedded in the base material will have good wear resistance, but the less exposed surface will reduce the hydrophobic effect; similarly, if the surface is enriched with too many nanoparticles, they will be easily destroyed in various ways due to the lack of strong interaction between them, and the wear resistance will be poor.

[0003] Therefore, in the field of wear resistance of hydrophobic coatings, how to enhance the hydrophobicity and wear resistance of super hydrophobic coatings under the premise of environmental protection is a technical problem that technicians in this field need to solve. Summary of the invention

[0004] In view of the above situation, the present invention provides a method for preparing a waterborne polyurethane super-hydrophobic composite coating, so as to enhance the hydrophobicity and wear resistance of the super-hydrophobic coating under the premise of environmental protection.

[0005] A method for preparing a waterborne polyurethane super-hydrophobic composite coating comprises the following steps:

[0006] Step (1): adding deionized water to a reactor, and adding concentrated sulfuric acid to dilute the solution while stirring, finally preparing sulfuric acid with a preset mass fraction, preheating the prepared sulfuric acid to 40-45° C., and slowly adding cellulose powder to the reactor while stirring, and stirring the mixture for 40-45 minutes until the solution turns yellowish, immediately taking out the reactor, and placing it in ice water at 2-5° C. to interrupt the acidolysis reaction;

[0007] Then the cooled solution is centrifuged, and the precipitate after centrifugation is taken to wash away the excess acid and over-reacted carbide until the pH is greater than 3. The washed precipitate is placed in a regenerated cellulose dialysis bag and dialyzed in ultrapure water with a resistivity of less than 18MΩ﹒cm until the pH is equal to 7, and then diluted with deionized water to obtain a nanocellulose dispersion;

[0008] Step (2): taking the prepared nanocellulose dispersion, washing away excess water with anhydrous ethanol, adding anhydrous ethanol as a solvent, and ultrasonically dispersing for 30 minutes, then adding nanoparticles with a mass concentration of 2 to 5%, and adding a silane modifier for modification, stirring for 6 to 12 hours at 25° C. to obtain a dispersion of nanocellulose loaded with hydrophobic nanoparticles; the particle size of the composite particles in the dispersion is 200 to 600 nm; wherein the mass concentration of the nanocellulose is 5 to 10%; and the amount of the silane modifier is 2 to 5% of the dispersion;

[0009] Step (3): diluting the waterborne polyurethane with butyl acetate, and then spraying it evenly on the substrate, placing it horizontally at room temperature for 30 to 60 minutes, spraying the dispersion of nanocellulose loaded hydrophobic nanoparticles obtained in step (2) on the waterborne polyurethane film, and drying it naturally at room temperature, and finally obtaining a waterborne polyurethane type super hydrophobic composite coating.

[0010] The preparation method of the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein, in step (1), the step of washing away excess acid adopts any one of deionized water cleaning acid, ammonia neutralizing acid, and sodium hydroxide neutralizing acid; for ammonia neutralizing acid or sodium hydroxide neutralizing acid, the resistivity of the dialysate is detected during dialysis until it no longer changes.

[0011] The preparation method of the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein, in step (1), when ammonia water is used to neutralize the acid in the step of washing away excess acid, the concentration of ammonia water used to neutralize the acid is 10%; when sodium hydroxide is used to neutralize the acid in the step of washing away excess acid, the molar concentration of sodium hydroxide is 0.1M.

[0012] The preparation method of the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein, in step (2), a silane coupling agent is first added as a connector between nanocellulose and nanoparticles, and after the reaction is completed, a silane modifier is added for subsequent reaction.

[0013] In the method for preparing the above-mentioned waterborne polyurethane type super-hydrophobic composite coating, the silane coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0014] The preparation method of the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein, in step (3), the ratio of water-based polyurethane to butyl acetate is 1:3; 2 to 4 mL of water-based polyurethane dilution and 1 to 4 mL of nanocellulose-loaded hydrophobic nanoparticle dispersion are sprayed per 12.5 square centimeters of substrate.

[0015] The preparation method of the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein the silane modifier is one or more of fluorine-free hydrophobic modifiers such as tridecyltrimethoxysilane, hexadecyltrimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

[0016] In the method for preparing the above-mentioned water-based polyurethane type super-hydrophobic composite coating, the nanoparticles are one or more of nano-silicon dioxide particles, nano-zinc oxide particles, nano-titanium dioxide particles, nano-calcium carbonate particles, and nano-tin oxide particles.

[0017] In the method for preparing the above-mentioned water-based polyurethane type super-hydrophobic composite coating, the cellulose powder is microcrystalline cellulose with a particle size of 25 μm or 65 μm.

[0018] The method for preparing the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein, in step (3), a spray gun is selected for spraying, and the spray gun pressure is 2 to 3 bar.

[0019] The preparation method of the above-mentioned water-based polyurethane type super-hydrophobic composite coating, wherein the substrate is any one of glass, wood, steel, and ceramic tiles.

[0020] According to the preparation method of the aqueous polyurethane type super-hydrophobic composite coating provided by the present invention, a long-chain-shaped nanocellulose is used, and a large amount of hydrophobic nanoparticles are loaded by utilizing the characteristics of its large specific surface area, which greatly enhances the hydrophobic effect of the coating; At the same time, nanocellulose is bonded to the aqueous polyurethane network, so that a large amount of hydrophobic nanoparticles are exposed to the surface with one end of the cellulose chain, and "take root" in the aqueous polyurethane, which greatly enhances its wear resistance. The present invention is relatively simple and nontoxic to prepare, can be mass-produced, and improves the problem of poor mechanical wear resistance of super-hydrophobic coating.

[0021] In addition, the present invention can be prepared by only a simple spraying method or a scraping method, without the need for time-consuming pretreatment steps, strict process conditions, expensive medicine bottles and equipment. The preparation process is simple and practical, the superhydrophobic effect is good and can reach 162.3°, the process is environmentally friendly, the production cost is low, and the adhesion and wear resistance on substrates such as glass, steel plates, and wood are strong, the versatility is strong, and large-area preparation and application are easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope photograph of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 1.

[0023] Figure 2 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 1.

[0024] Figure 3 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 2.

[0025] Figure 4 This is a scanning electron microscope photograph of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 3.

[0026] Figure 5 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 3.

[0027] Figure 6 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 4.

[0028] Figure 7This is a picture of the water contact angle of the water-based polyurethane super-hydrophobic composite coating prepared in Example 5.

[0029] Figure 8 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 6.

[0030] Fig. 9 This is a scanning electron microscope photograph of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 7.

[0031] Fig.10 This is a picture of the water contact angle of the water-based polyurethane super-hydrophobic composite coating prepared in Example 7.

[0032] Fig.11 This is a scanning electron microscope photograph of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 8.

[0033] Fig.12 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 8.

[0034] Fig.13 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 9.

[0035] Fig.14 This is a picture of the water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 10.

[0036] Fig.15 This is a relationship diagram between tape peeling and water contact angle of the water-based polyurethane super-hydrophobic composite coating prepared in Example 10.

[0037] Fig.16 This is a relationship diagram between tape peeling and water contact angle of the water-based polyurethane super-hydrophobic composite coating prepared in Example 11.

[0038] Fig.17 This is a graph showing the relationship between sandpaper friction and water contact angle of the waterborne polyurethane super-hydrophobic composite coating prepared in Example 11. DETAILED DESCRIPTION

[0039] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to various embodiments, but the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0041] Example 1

[0042] A method for preparing a waterborne polyurethane super-hydrophobic composite coating comprises the following steps:

[0043] Step (1), acid hydrolyzing microcrystalline cellulose to prepare nanocellulose

[0044] 42.3 mL of deionized water was measured into a volumetric flask, and then 77.7 mL of concentrated sulfuric acid with a mass fraction of 98% was slowly added while stirring with a glass rod. After cooling to room temperature in a cold water bath, 5.0 g of cellulose powder with a particle size of 25 μm was slowly added to the prepared sulfuric acid solution in sequence, and a magnetic particle was loaded. The oil bath was preheated to 45°C and reacted in an oil bath at 45°C for 45 minutes. After the reaction, the mixture was quickly cooled with an ice water bath and centrifuged at 10,000 rpm for 30 minutes, and washed with water until the pH reached above 3, and the centrifugation was terminated. The contents were transferred to a regenerated cellulose dialysis bag with a molecular weight cutoff of 3500, and dialyzed in ultrapure water with a resistivity of less than 18.0 MΩ﹒ cm until the pH reached 7 and the dialysis was completed to obtain a nanocellulose dispersion.

[0045] Step (2), preparation of nanocellulose-loaded nanosilica particles

[0046] 40 mL of the prepared nanocellulose was taken out and washed with anhydrous ethanol to remove moisture, then added to a reagent bottle and anhydrous ethanol was added to 120 mL, 5 mL of ammonia water, 4 mL of tetraethyl silicate (TEOS), and 8 mL of hexadecyltrimethoxysilane (HDTMS) were added, ultrasonicated at 100 W for 6 hours and transferred to 450 rpm for reaction for 6 hours to obtain a nanocellulose-loaded hydrophobic nano-silica particle dispersion (CH-SiO2-CNCs).

[0047] Step (3), preparation of waterborne polyurethane type super-hydrophobic composite coating

[0048] Measure 10 mL of waterborne polyurethane and add 30 mL of butyl acetate, and ultrasonicate until uniformly diluted. Weigh 5 mL of waterborne polyurethane dilution with a measuring cylinder, adjust the spray gun pressure to 2-3 bar, and spray the dilution evenly on the glass plate and tinplate sheet (2.5*2.5 cm). Place the sprayed glass plate and tinplate sheet horizontally at room temperature for one hour. When the polyurethane film is in a semi-dry state, spray 3.00 mL of hydrophobically modified nanocellulose-loaded nano-silica particle dispersion evenly on the polyurethane film and dry it at room temperature.

[0049] The base material layer of this embodiment is glass and tinplate, and the glass plate and tinplate are cleaned and dried. The following embodiments are the same and will not be repeated.

[0050] The coating was analyzed by scanning electron microscopy (SEM) and contact angle test, and the results were as follows: Figure 1 and Figure 2 .Depend on Figure 1 It can be seen that the nano-silica particles are attached to the nano-cellulose to form a "cauliflower"-like structure. The surface of this composite coating is a rough multi-level structure. Figure 2 It can be seen that the contact angle of the prepared composite coating reached 161°, achieving a relatively good superhydrophobic effect.

[0051] The composite coating obtained in this embodiment includes a hydrophobic layer, a water-based polyurethane transition layer and a base material layer. The hydrophobic layer, the water-based polyurethane transition layer and the base material layer are sprayed using a multi-step spraying process, and the water-based polyurethane layer is embedded with part of nanocellulose and hydrophobic nanoparticles, which improves the compatibility between the two layers and enhances the adhesion performance of the hydrophobic coating.

[0052] Example 2

[0053] This embodiment is basically the same as embodiment 1, except that when preparing nanocellulose, the method of removing excess acid is changed from washing with deionized water to neutralization with ammonia water, and the neutralization process is added dropwise to ensure that the precipitation temperature is not too high, thereby obtaining nanocellulose in this case. Figure 3 It can be seen that the prepared composite coating is a superhydrophobic coating with a contact angle of 160.2°.

[0054] Example 3

[0055] A waterborne polyurethane super-hydrophobic composite coating comprises the following steps:

[0056] Step (1), acid hydrolyzing microcrystalline cellulose to prepare nanocellulose

[0057] 55.0mL of deionized water was measured into a volumetric flask, and then 65.0mL of concentrated sulfuric acid with a mass fraction of 98% was slowly added while stirring with a glass rod. After cooling to room temperature in a cold water bath, 4.0g of cellulose powder with a particle size of 25μm was slowly added to the prepared sulfuric acid solution in sequence, and a magnetic particle was loaded. The oil bath was preheated to 50℃ and reacted in a 50℃ oil bath for 65 minutes. After the reaction, the temperature was quickly cooled with an ice water bath and centrifuged at 10000rpm for 40 minutes, and washed with water until the pH reached above 3 and the centrifugation was terminated. The contents were transferred to a regenerated cellulose dialysis bag with a molecular weight cutoff of 3500, and dialyzed in ultrapure water with a resistivity of less than 18.0MΩ﹒cm until the pH reached 7 and the dialysis was completed. A nanocellulose dispersion was obtained.

[0058] Step (2), preparation of nanocellulose-loaded nano-titanium dioxide particles

[0059] Take out 40mL of the prepared nanocellulose and add it directly to a reagent bottle and add anhydrous ethanol to 120mL. After ultrasonic dispersion, add 2.0g of nano-titanium dioxide with a particle size of 25-40nm, and adjust the pH to 4 with acetic acid. After ultrasonication for one hour, add 8mL of hexadecyltrimethoxysilane (HDTMS) and stir at 800rpm at 25℃ for 24 hours. Wash it three times with anhydrous ethanol, put it in 30mL of anhydrous ethanol and ultrasonicate it for 60min to obtain a hydrophobic nanocellulose-loaded nano-titanium dioxide particle dispersion (CH-TiO2-CNCs).

[0060] Step (3), preparation of waterborne polyurethane type super-hydrophobic composite coating

[0061] Measure 10mL of waterborne polyurethane and add 30mL of butyl acetate, and ultrasonicate until uniformly diluted. Weigh 5mL of waterborne polyurethane dilution with a measuring cylinder, adjust the spray gun pressure to 2-3bar, and spray the dilution evenly on the glass plate and tinplate sheet (2.5*2.5cm). Place the sprayed glass plate and tinplate sheet horizontally at room temperature for one hour. When the polyurethane film is in a semi-dry state, spray 3.00mL of hydrophobically modified nanocellulose-loaded nano-titanium dioxide particle dispersion evenly on the polyurethane film and dry it at room temperature.

[0062] The coating was characterized by SEM and tested for contact angle. The analysis results are as follows: Figure 4 and Figure 5 The SEM microscopic surface shows that the rod-shaped nano-titanium dioxide is not arranged in an orderly manner, but its distribution is relatively dense, and a multi-level rough structure can be achieved, so the hydrophobic effect is quite good. Figure 5 It can be seen that its water contact angle is 157.9°.

[0063] Example 4

[0064] This embodiment is basically the same as embodiment 3, except that when preparing nanocellulose, the method of removing excess acid is changed from washing with deionized water to neutralization with ammonia water, and the neutralization process is added dropwise to ensure that the precipitation temperature is not too high, thereby obtaining nanocellulose in this case. Figure 6 It can be seen that the prepared composite coating is a superhydrophobic coating, and its water contact reaches 156.5°.

[0065] Example 5

[0066] This embodiment is basically the same as embodiment 3, except that when preparing nanocellulose, the method of removing excess acid is changed from washing with deionized water to neutralization with 0.1M sodium hydroxide, which is added dropwise during the neutralization process to ensure that the precipitation temperature is not too high, thereby obtaining nanocellulose in this case. Figure 7 It can be seen that the prepared composite coating is a superhydrophobic coating, and its water contact reaches 158.5°.

[0067] Example 6

[0068] This embodiment is basically the same as embodiment 1, except that when preparing nanocellulose, the method of removing excess acid is changed from washing with deionized water to neutralization with 0.1M sodium hydroxide, which is added dropwise during the neutralization process to ensure that the precipitation temperature is not too high, thereby obtaining nanocellulose in this case. Figure 8 It can be seen that the prepared composite coating is a superhydrophobic coating, and its water contact reaches 156.9°.

[0069] Example 7

[0070] This example is basically the same as Example 3, except that when preparing nanocellulose-loaded nano zinc oxide particles, nano titanium dioxide is replaced with nano zinc oxide, and the pH is adjusted to 10 by ammonia water and then ultrasonically dispersed before reacting, thereby obtaining a hydrophobic nanocellulose-loaded nano zinc oxide particle dispersion. The coating was characterized by SEM and tested for contact angle, and the analysis results are as follows: Fig. 9 and Fig.10 The SEM microscopic surface shows that the nano-zinc oxide has some aggregation. Although its structure is similar to the papillae on the surface of lotus leaves, the micro-aggregated nano-zinc oxide is more scattered and is easy to transform into the Wenzel model, resulting in a poorer hydrophobic effect. Fig.10 It can be seen that its water contact angle is only 155.5°.

[0071] Example 8

[0072] A method for preparing a waterborne polyurethane super-hydrophobic composite coating comprises the following steps:

[0073] Step (1), acid hydrolyzing microcrystalline cellulose to prepare nanocellulose

[0074] 50.0mL of deionized water was measured into a volumetric flask, and then 70.0mL of concentrated sulfuric acid with a mass fraction of 98% was slowly added while stirring with a glass rod. After cooling to room temperature in a cold water bath, 4.0g of cellulose powder with a particle size of 65μm was slowly added to the prepared sulfuric acid solution in sequence, and a magnetic particle was loaded. The oil bath was preheated to 45℃ and reacted in a 45℃ oil bath for 65 minutes. After the reaction, the temperature was quickly cooled with an ice water bath and centrifuged at 10000rpm for 30 minutes, and washed with water until the pH reached above 3 and the centrifugation was terminated. The contents were transferred to a regenerated cellulose dialysis bag with a molecular weight cutoff of 3500, and dialyzed in ultrapure water with a resistivity of less than 18.0MΩ﹒cm until the pH reached 7 and the dialysis was completed. A nanocellulose dispersion was obtained.

[0075] Step (2), preparation of nanocellulose-loaded nanosilica particles

[0076] 40 mL of the prepared nanocellulose was taken out and washed with anhydrous ethanol to remove moisture, then added to a reagent bottle and anhydrous ethanol was added to 120 mL. After ultrasonic dispersion, 2.0 g of nano-silicon dioxide with a particle size of 50 nm was added, and the pH was adjusted to 10 with ammonia water. After ultrasonication for half an hour, 8 mL of hexadecyltrimethoxysilane (HDTMS) and 2 mL of 3-(2,3-epoxypropoxy)propyltrimethoxysilane were added, and stirred at 800 rpm for 12 hours at 25 ° C. Washed three times with a mixture of deionized water and anhydrous ethanol, placed in 40 mL of anhydrous ethanol and ultrasonicated for 60 minutes to obtain a hydrophobic nanocellulose-loaded nanosilica particle dispersion (CH-SiO2-CNCs).

[0077] Step (3), preparation of waterborne polyurethane type super-hydrophobic composite coating

[0078] Measure 10 mL of waterborne polyurethane and add 30 mL of butyl acetate, and ultrasonicate until uniformly diluted. Weigh 5 mL of waterborne polyurethane dilution with a measuring cylinder, adjust the spray gun pressure to 2-3 bar, and spray the dilution evenly on the glass plate and tinplate sheet (2.5*2.5 cm). Place the sprayed glass plate and tinplate sheet horizontally at room temperature for one hour. When the polyurethane film is in a semi-dry state, spray 3.00 mL of hydrophobically modified nanocellulose-loaded nano-silica particle dispersion evenly on the polyurethane film and dry it at room temperature.

[0079] The coating was characterized by SEM and tested for contact angle. The analysis results are as follows: Fig.11 and Fig.12 The SEM microscopic surface shows that compared with the case without adding coupling agent, its surface is smoother, with fewer defects and the film is denser. Fig.12 The water contact angle is as high as 163.9°.

[0080] Example 9

[0081] This embodiment is basically the same as embodiment 8, except that when preparing nanocellulose-loaded nano zinc oxide particles, nano silicon dioxide is replaced with nano zinc oxide, and the use of nanocellulose does not require the removal of excess water. The pH is adjusted to 10 and ultrasonic dispersion is performed before the reaction. At the same time, when preparing nanocellulose, the method of removing excess acid is changed from washing with deionized water to neutralization with ammonia water. The neutralization process is added dropwise to ensure that the precipitation temperature is not too high, thereby obtaining a hydrophobic nanocellulose-loaded nano zinc oxide particle dispersion. Fig.13 It can be seen that the prepared composite coating is a superhydrophobic coating, and the water contact reaches 158.2°.

[0082] Example 10

[0083] This embodiment is basically the same as embodiment 9, except that when preparing nanocellulose, the method of removing excess acid is changed from washing with deionized water to neutralization with 0.1M sodium hydroxide, which is added dropwise during the neutralization process to ensure that the precipitation temperature is not too high, thereby obtaining nanocellulose in this case. Fig.14 It can be seen that the prepared composite coating is a super hydrophobic coating, and the water contact reaches 158.9°. 3M tape is attached to this coating. Fig.15 It can be seen that the composite coating has good hydrophobicity after the tape has been removed multiple times, which proves that the composite coating has good adhesion.

[0084] Embodiment 11

[0085] This embodiment is basically the same as embodiment 8, except that tridecyl trimethoxysilane is used to modify the nanoparticles, and its hydrophobic effect is not significantly different from that of embodiment 8. We attached 3M tape to this coating. Fig.16 It can be seen that the composite coating has good hydrophobicity after the tape is torn off many times. At the same time, a 50g weight is repeatedly applied to a 1000-grit sandpaper for sandpaper abrasion test. Fig.17 It can be seen that the coating performance is good under the wear test, which proves that the composite coating has good wear resistance.

[0086] In summary, according to the preparation method of the aqueous polyurethane type super-hydrophobic composite coating provided by the present invention, a long-chain-shaped nanocellulose is used, and a large amount of hydrophobic nanoparticles are loaded using the characteristics of its large specific surface area, which greatly enhances the coating hydrophobic effect; At the same time, nanocellulose is bonded to the aqueous polyurethane network, so that a large amount of hydrophobic nanoparticles are exposed to the surface with one end of the cellulose chain, and "take root" in aqueous polyurethane, greatly enhancing its wear resistance. The present invention is relatively simple and nontoxic to prepare, can be mass-produced, and improves the problem of poor mechanical wear resistance of super-hydrophobic coating.

[0087] In addition, the present invention can be prepared by only a simple spraying method or a scraping method, without the need for time-consuming pretreatment steps, strict process conditions, expensive medicine bottles and equipment. The preparation process is simple and practical, the superhydrophobic effect is good and can reach 162.3°, the process is environmentally friendly, the production cost is low, and the adhesion and wear resistance on substrates such as glass, steel plates, and wood are strong, the versatility is strong, and large-area preparation and application are easy to achieve.

[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a waterborne polyurethane type super-hydrophobic composite coating, characterized in that: The following steps are involved: Step (1): adding deionized water to a reactor, and adding concentrated sulfuric acid to dilute the solution while stirring, finally preparing sulfuric acid with a preset mass fraction, preheating the prepared sulfuric acid to 40-45° C., and slowly adding cellulose powder to the reactor while stirring, and stirring the mixture for 40-45 minutes until the solution turns yellowish, immediately taking out the reactor, and placing it in ice water at 2-5° C. to interrupt the acidolysis reaction; Then the cooled solution is centrifuged, and the precipitate after centrifugation is taken to wash away the excess acid and over-reacted carbide until the pH is greater than 3. The washed precipitate is placed in a regenerated cellulose dialysis bag and dialyzed in ultrapure water with a resistivity of less than 18MΩ﹒cm until the pH is equal to 7, and then diluted with deionized water to obtain a nanocellulose dispersion; Step (2): taking the prepared nanocellulose dispersion, washing away excess water with anhydrous ethanol, adding anhydrous ethanol as a solvent, and ultrasonically dispersing for 30 minutes, then adding nanoparticles with a mass concentration of 2 to 5%, and adding a silane modifier for modification, stirring for 6 to 12 hours at 25° C. to obtain a dispersion of nanocellulose loaded with hydrophobic nanoparticles; the particle size of the composite particles in the dispersion is 200 to 600 nm; wherein the mass concentration of the nanocellulose is 5 to 10%; and the amount of the silane modifier is 2 to 5% of the dispersion; Step (3): diluting the waterborne polyurethane with butyl acetate, and then spraying it evenly on the substrate, placing it horizontally at room temperature for 30 to 60 minutes, spraying the dispersion of nanocellulose loaded hydrophobic nanoparticles obtained in step (2) on the waterborne polyurethane film, and drying it naturally at room temperature, and finally obtaining a waterborne polyurethane type super hydrophobic composite coating.

2. The method for preparing an aqueous polyurethane type super-hydrophobic composite coating according to claim 1, wherein: In step (1), in the step of washing away excess acid, any one of deionized water washing acid, ammonia neutralized acid, and sodium hydroxide neutralized acid is used; for ammonia neutralized acid or sodium hydroxide neutralized acid, the resistivity of the dialysate is tested during dialysis until it no longer changes.

3. The preparation method of the aqueous polyurethane type super-hydrophobic composite coating according to claim 2, characterized in that, In step (1), when ammonia water is used to neutralize the acid in the step of washing away excess acid, the concentration of ammonia water used to neutralize the acid is 10%; when sodium hydroxide is used to neutralize the acid in the step of washing away excess acid, the molar concentration of sodium hydroxide is 0.1M.

4. The preparation method of the waterborne polyurethane type super-hydrophobic composite coating according to claim 1, characterized in that, In step (2), a silane coupling agent is first added as a connector between nanocellulose and nanoparticles, and after the reaction is completed, a silane modifier is added for subsequent reaction.

5. The method for preparing an aqueous polyurethane type super-hydrophobic composite coating according to claim 4, wherein: The silane coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.

6. The method for preparing the waterborne polyurethane type super-hydrophobic composite coating according to claim 1, characterized in that: In step (3), the ratio of aqueous polyurethane to butyl acetate is 1:3; 2 to 4 mL of aqueous polyurethane dilution and 1 to 4 mL of nanocellulose-loaded hydrophobic nanoparticle dispersion are sprayed on every 12.5 square centimeters of substrate.

7. The method for preparing the waterborne polyurethane type super-hydrophobic composite coating according to claim 1, characterized in that: The silane modifier is one or more of fluorine-free hydrophobic modifiers such as tridecyltrimethoxysilane, hexadecyltrimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

8. The method for preparing the waterborne polyurethane type super-hydrophobic composite coating according to claim 1, characterized in that, The nanoparticles are one or more of nano silicon dioxide particles, nano zinc oxide particles, nano titanium dioxide particles, nano calcium carbonate particles, and nano tin oxide particles.

9. The method for preparing the waterborne polyurethane type super-hydrophobic composite coating according to claim 1, wherein: The cellulose powder is microcrystalline cellulose with a particle size of 25 μm or 65 μm.

10. The method for preparing the waterborne polyurethane type super-hydrophobic composite coating according to claim 1, characterized in that: In step (3), a spray gun is used for spraying, and the spray gun pressure is 2 to 3 bar.

Citation Information

Patent Citations

  • Super-hydrophobic composite coating, and preparation method and application thereof

    CN108017958A

  • Method of preparing super-hydrophobic coating by compounding waterborne polyurethane and hydrophobic modified inorganic nanoparticles

    CN109370408A

  • Plastic particles for water surface oil fouling recovery treatment

    CN110790973A